Pengaruh Marketing Mix (4P) terhadap Loyalitas Konsumen pada Mini market Indomaret dan Alfamart di Kota Pematangsiantar - Suhendro, Dedi (Universitas Medan Area, 2019)
This study aims to determine the effect of independent variables both simultaneously and partially on the dependentt variable. The research population of the population of Pematangsiantar has a population of 247,411 people. From the Slovin formula, the sample used in this study was purposive sampling selected with terms and criteria to be sampled. Whereas the selection that does not meet the requirements and criteria is not sampled. The research sample was 100 people. Research data was processed using SPSS. The hypothesis results prove that the independent variables of Marketing Mix (Product Location, Promotion and Price) simultaneously have no significant effect on the dependentt variable (Consumer Loyalty) on the Indomaret and Alfamart Mini market in Pematangsiantar City. While partially the product does not affect consumer loyalty. Location does not affect consumer loyalty. Promotion does not affect consumer loyalty and price does not affect consumer loyalty at the Indomaret and Alfamart mini markets in Pematangsiantar City.